PENGARUH PERSEPSI AUDITOR INSPEKTORAT KOTAMADYA METRO TENTANG INDEPENDENSI DAN PROFESIONALISMA TERHADAP EFEKTIVITAS PEMERIKSAAN - Eka Nurzanah; Sugiarto Sugiarto; Sunarmi Sunarmi (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2021)
This research aims to find out the effect of inspectorate auditor perception of metro municipality concerning independence and professionalism to inspection effectiveness. The research hypothesis study whether the inspectorate auditor perception of metro municipality concerning independence and professionalism simultaneously affect to inspection effectiveness. The population of this research is inspector auditor who works at Inspectorate of Metro Municipality. The independent variable of this research is independence and professionalism. Data of this research is primary data obtained through spreading questioners directly to inspector auditor at Inspectorate of Metro Municipality. Analysis model used to study hypothesis is multiple linier regression, it based on data from thirty respondents which its research through questioners. The result showed that independence and professionalism simultaneously and partially affect significantly to inspection effectiveness on auditor at Inspectorate of Metro Municipality.